A novel derivative of picolinic acid induces endoplasmic reticulum stress-mediated apoptosis in human non-small cell lung cancer cells: synthesis, docking study, and anticancer activity - Ali H. Abbas; Ammar A. Razzak Mahmood; Lubna H. Tahtamouni; Zainab A. Al-Mazaydeh; Majdoleen S. Rammaha; Fatima Alsoubani; Rheda I. Al-bayati (Pensoft Publishers, 2021)
Thirteen new derivatives of picolinic acid (4-7) were designed and synthesized from the starting parent molecule, picolinic acid. The new compounds were characterized by ATR-FTIR, 1HNMR, and CHNS analysis. A molecular docking study was performed to evaluate the binding affinity of the synthesized compounds toward EGFR kinase domain that indicated occupation of the critical site of EGFR kinase pocket and excellent positioning of the compounds in the pocket. The cytotoxic activity of the compounds against two human cancer cell lines (A549 and MCF-7), the non-tumorigenic MCF10A cell line, and white blood cells (WBC) was evaluated using the MTT assay. Compound 5 showed anticancer activity against A549 lung cancer cells (IC50 = 99.93 µM) but not against MCF-7 breast cancer cells or normal cells. Compound 5 mediated cytotoxicity in A549 lung cancer cells by inducing apoptotic cell death, as suggested by fragmented nuclei after DAPI staining, and agarose gel electrophoresis. Moreover, compound 5 triggered the activation of caspases 3, 4 and 9. However, compound 5 treatment did not affect the release of cytochrome c from the mitochondria to the cytosol, as compared to the vehicle-treated control cells. Nevertheless, compound 5-treated cells reported greater release of smac/DIABLO to the cytosol. In the same context, both compound 5 and thapsigargin (specific inhibitor of sarco/endoplasmic reticulum Ca2+-ATPase (SERCA)) enhanced eIF2 phosphorylation, reflecting the activation of the atypical ER stress pathway and the potential applicability of compound 5 in lung cancer treatment.